2017
DOI: 10.1002/2016jf004130
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the transport, distribution, and budget of 210Pb in sediment over the estuarine and inner shelf areas of the East China Sea due to Changjiang catchment changes

Abstract: To investigate the impact of changes in the Changjiang catchment on the estuarine coast‐shelf sedimentary system, variations in the transport, distribution, and budget of 210Pb in the sediment of the Changjiang subaqueous delta (CSD) and the Zhejiang‐Fujian coastal mud belt (ZFCMB) system were analyzed before and after the impounding of the Three Gorges Dam (TGD). The results indicate that the 210Pbex activity in the surficial sediments of the CSD‐ZFCMB decreased significantly after 2003 and that the surficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…[] successfully constructed the mass budget of black carbon in the BS, and Gao et al . [] developed a preliminary estimate of the 210 Pb budget for the ECS. However, relevant studies in large‐scale marginal sea systems are scarce.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[] successfully constructed the mass budget of black carbon in the BS, and Gao et al . [] developed a preliminary estimate of the 210 Pb budget for the ECS. However, relevant studies in large‐scale marginal sea systems are scarce.…”
Section: Resultsmentioning
confidence: 99%
“…An export ratio of sediments was defined and calculated as export flux divided by input flux. We calculated an export ratio of 21%, which is very close to the value of 20% proposed by Gao et al [2017]. Thus, the mass budget of PAHs for the ECMSs highlights the fate of PAHs on an extended regional scale and further clarifies the importance of PAHs transportation among subregions of the ECMSs.…”
Section: Deposition Flux Of Pahs In the Ecmssmentioning
confidence: 99%
“…Grain-size variations from 1982-2014 showed that sediment coarsening occurred not only in the Changjiang Estuary but had also expanded to the entire estuarineinner shelf areas (Gao et al, 2019). Previous studies also demonstrated that material deposited in the estuarine-inner shelf regions of the ECS was likely to lag behind changes in the Changjiang River catchment by about 3 years (Gao et al, 2017;Hu et al, 2012). Therefore, samples collected in 2006 could reflect the sedimentary environment in the CSD around 2003, representing the situation before the construction of the TGD.…”
Section: Variations In Sediment Grain Size In Response To Human-inducmentioning
confidence: 97%
“…In addition to dam construction, the Water and Soil Conservation Project implemented in the high sediment yield region of the upper Changjiang basin in the 1980s could be another factor resulting in abrupt reductions in sediment loads (Dai & Lu, ). Such drastic reductions in sediment discharge have caused significant changes in the sedimentary environment and hydrodynamics of the ECS's estuarine‐inner shelf regions (Gao et al, ; Wang et al, ; Yang et al, ). In addition, reservoir interception of coarse‐grained sediment from upper reaches has induced channel erosion in the middle and lower reaches, substantially changing the sediment component reaching the ECS (Gao et al, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the sediments from the Luan River and Hai River are deposited in the central Bohai Bay, and clay particles are derived to the southeastern region (Hu et al 2010) where the 239+240 Pu activities are significantly higher than other areas (Zhuang et al 2019). Moreover, the Yangtze River also carries a large amount of sediments deposited in the Yangtze River estuary, and forms two large-scale mud deposits (Changjiang Subaqueous Delta and Zhejiang-Fujian Coastal Mud Belt) (Gao et al 2017). The two mud deposits have exceptionally higher 239+240 Pu activities and 240 Pu/ 239 Pu atom ratios than their surroundings.…”
Section: Long-range Transport Of Pu From the Ppgmentioning
confidence: 99%